Late Neolithic Hilltop Communities in Central Kujawy - Kośko, Aleksander; Szmyt, Marzena (Faculty of Archaeology, Adam Mickiewicz University in Poznań, 2021)
The article presents the history and the most important results of archaeological research on the so-called Prokopiak’s Mount at Opatowice in the Kujawy region. Archaeologists from the Adam Mickiewicz University conducted surveys and excavations there for several years - from 1983 to 1998. Remains of settlements and graves discovered on the hill come mainly from the 4 th and 3 rd mill. BC and represent several units of the archaeological taxonomy: the Funnel Beaker culture, the Globular Amphora culture, the Corded Ware culture, the Neman culture, and the Proto-Bronze group. Since 2006, a special series of monographs of individual sites has been published. To date, five volumes have been published, and more are being prepared. Thanks to meticulous investigations as well as comprehensive and multifaceted scientific analyzes, the Prokopiak’s Mount at Opatowice is one of the best-recognized micro-regions of Late Neolithic settlement in Kujawy and is a reference point for extensive comparative research. This applies, for example, to the local scale of absolute chronology, various components of material culture, forms of settlements and camps, ceremonial and funeral practices, as well as economic activities.
Keywords: Late Neolithic; Kujawy region; 4 th and 3 rd millennium BC; settlement practices; funeral practices